The Environmental law of the Kurdistan Region, and its compatibility with international principles of environmental policies: Environmental law of the Kurdistan Region - Salam Abdulqadir Abdulrahman, (Technium Social Sciences Journal, 2020)
Environmental problems in Iraqi Kurdistan Region have been growing over the past two decades, and the regional government has responded by issuing legislation and regulation. This paper reviews the Kurdistan Regional environmental laws, and evaluates them against the international principles of environmental policies. It finds that the laws have incompatibility with the principles to varying degrees. The paper suggests that incorporating these principles into the environmental laws is necessary so as to have a just, participatory and precautionary environmental policy and a sustainable economy. The paper also looks at some environmental problems on the ground to further clarify the matter.